P625 Characteristics of SARS-CoV-2 infection in IBD patients in the second and third wave compared with the first wave and with the data of general population. (27th May 2021) - Guerra Marina, I; Algaba, A; Castro, S; Jiménez, L; Garza, D; Aller, M D M; Granja, A; Guardiola, A; Gil, M; Ruiz, P; Bermejo, F
Abstract: Background: Our aims were: 1.) to compare the characteristics of SARS-CoV-2 infection in IBD patients in the second and third wave with respect to the results published in our site in the first wave (I. Guerra et al. Inflamm Bowel Dis. 2021 Jan 1;27(1):25–33) and 2.) to compare the date of the second and third wave with data of general population from the Autonomous Community of Madrid Methods: Cohort, observational study in IBD patients followed in our IBD Unit with SARS-CoV-2 infection between March 2020 and May 2020 (first wave) and between July 2020 to March 2021 (second-third wave). All data were collected by telephone interview and reviewing the electronical medical records Results: The demographic characteristics of the patients included are shown in Table 1. Regarding clinical features of SARS-CoV-2 infection in both group of patients are represented in Table 2. The severity of disease was not related to immunomodulators and/or biological treatments in both cohorts. The number of COVID-19 cases by date in our IBD Unit in comparison with the cases in the Community of Madrid are shown in the Figure 1. Conclusion: The patients diagnosed in the first wave were older and more symptomatic. Although the number of severe cases was higher in the first wave, influenced by the limited availability of tests in that period, no difference was found in mortality or in the percentage of ICU admissions.Severity of SARS-CoV-2 infection was not related to immunosuppression and in the second-third wave the IBD treatment was maintained more frequently.The distribution of cases in our series was in concordance with the data obtained in the general population.